You cannot have both – Two different ways of change implementation and their effects on adaptive performance and frustration - Roling, Wiebke M.; Grum, Marcus; Gronau, Norbert; Kluge, Annette (International journal of industrial ergonomics, 2024)
The dynamics and frequency of change in today's workplaces force organizations to address the question of how to create optimal conditions for facilitating adaptation to change. Identifying critical factors that affect performance and well-being in change situations can help answer this question. Given the need for applied research in this area, the aim of this paper is to investigate whether the way of change implementation has an impact on performance and well-being. Additionally, retentivity and specific self-efficacy as individual factors are exploratorily investigated. In an experimental study, seventy-one participants learned and trained specific manufacturing steps in a simulated production environment. Subsequently, they had to adapt the trained task execution as some of the previously learned manufacturing steps were subject to change. The changes were implemented a) either in a stepwise manner or b) all at once. The executed manufacturing steps were recorded, enabling the calculation of task execution time and classification of adaptation errors. The results of Mann-Whitney-U-tests showed that the stepwise introduction of changes led to significantly faster task execution time than the change introduction all at once. Additionally, descriptive statistics indicated fewer adaptation errors but higher frustration. Our exploratory analysis showed a significant negative relationship between retentivity and task execution time, as well as between specific self-efficacy and frustration. Stepwise change introduction seems to be beneficial for adaptation, even though emotional responses and individual factors must be considered. •This study used a close-to-real but standardized simulation setting to investigate the effects of two different ways of change implementation on adaptive performance and frustration.•Stepwise introduction of changes led to significantly faster task execution time compared to a change introduction all at once.•Descriptive statistics indicated that stepwise introduction of changes led to fewer adaptation errors, but higher frustration compared to a change introduction all at once.•Higher retentivity was significantly related to faster task execution time, and higher specific self-efficacy was significantly related to lower frustration.•The way of change implementation as well as individual factors and their effects on adaptive performance and frustration should be considered in organizational system design and change management.